Atherogenic circulating lipoproteins in ischemic stroke - Benitez, Sonia; Puig, Núria; Camps-Renom, Pol; Sánchez-Quesada, José Luis (Frontiers in Cardiovascular Medicine, 2024)
The fundamental role of qualitative alterations of lipoproteins in the early development of atherosclerosis has been widely demonstrated. Modified low-density lipoproteins (LDL), such as oxidized LDL (oxLDL), small dense LDL (sdLDL), and electronegative LDL [LDL(-)], are capable of triggering the atherogenic process, favoring the subendothelial accumulation of cholesterol and promoting inflammatory, proliferative, and apoptotic processes characteristic of atherosclerotic lesions. In contrast, high-density lipoprotein (HDL) prevents and/or reverses these atherogenic effects. However, LDL's atherogenic and HDL's anti-atherogenic actions may result altered in certain pathological conditions. The molecular mechanisms underlying the impaired effects of altered lipoproteins have been studied in numerous in vitro and in vivo studies, and have been extensively analyzed in coronary atherosclerosis, especially in the context of pathologies such as dyslipidemia, diabetes, obesity, and metabolic syndrome. However, the corresponding studies are scarcer in the field of ischemic stroke, despite carotid arteriosclerosis progression underlies at least 20% of ischemic strokes. The present review relates qualitative alterations of LDL and HDL with the development of carotid arteriosclerosis and the occurrence of ischemic stroke.